Antibacterial Activity of pH-Dependent Biosynthesized Silver Nanoparticles against Clinical Pathogen. (20th May 2014) - Chitra, Kethirabalan; Annadurai, Gurusamy
Abstract : Simple, nontoxic, environmental friendly method is employed for the production of silver nanoparticles. In this study the synthesized nanoparticles UV absorption band occurred at 400 nm because of the surface Plasmon resonance of silver nanoparticles. The pH of the medium plays important role in the synthesis of control shaped and sized nanoparticles. The colour intensity of the aqueous solution varied with pH. In this study, at pH 9, the colour of the aqueous solution was dark brown, whereas in pH 5 the colour was yellowish brown; the colour difference in the aqueous solution occurred due to the higher production of silver nanoparticles. The antibacterial activity of biosynthesized silver nanoparticles was carried out against E. coli . The silver nanoparticles synthesized at pH 9 showed maximum antibacterial activity at 50  μ L.